Knowledge, attitude and practice of good nutrition among women of childbearing age in Somolu Local Government, Lagos State - Ooreoluwa Fasola; Olayinka Abosede; Foluke A. Fasola (Journal of Public Health in Africa, 2018)
Women of child-bearing age (especially pregnant and lactating women) are in the most nutritionally-vulnerable stages of the life cycle. The aim of this study was to assess the knowledge, attitude and practice of good nutrition among women of childbearing age in Somolu Local Government (LG), Lagos state. This study was a cross-sectional descriptive survey of 244 women of childbearing age (15-49 years). Excellent knowledge and good attitude towards good nutrition was observed among 61.89% and 86.89% respectively. During pregnancy, greater than 80% took folic acid, iron supplements and increased daily consumption of fruits and vegetables while 43.59% avoided eggs, fish, meat and chocolate beverage because of taboos. Seven days prior to interview, over 90% had consumed fast foods, 56.15% and 50.01% of the respondents ate fruits and vegetables every day to ≥ 4 times in a day respectively. A majority of the respondents knew and had a good attitude towards good nutrition supporting studies from Kenya and Northern Nigeria. This, however, did not translate to good practice for about half of the respondents.